Aplicación de herramientas y técnicas de administración financiera para la Constructora e Inmobiliaria Proinjar S.A de la ciudad de Loja periodo 2012-2013 - Asanza Mendez., Vanessa Rosa (2016)
This research was conducted in order to comply with the general objective of; Apply Tools and Techniques of Financial Management for the Construction and Real Estate PROINJAR SA, period 2012-2013, which was necessary to meet specific objectives and apply vertical analysis and the States General Income Statement for the financial situation of the company; perform horizontal analysis of the balance sheet and income statements to determine the variations of the accounts that have suffered from one period to another; Apply financial ratios as indicators of profitability, liquidity, leverage, activity based on the financial statements of "PROINJAR" the years 2012-2013, Determine Leverage on fixed assets, funds and the Construction costs have to check the performance in sales and therefore profits; Structuring sales forecasts and preform statements for future events that are the basis for decision making, establish the equilibrium point for total sales if the company performs cover the costs and minimize the risks and leverage resources. For the execution of the work was necessary to use methods and techniques that allowed for a vertical analysis, horizontal, indicators, operating leverage and then make the balance point and execute statements preforms. The application of tools and techniques of financial management allowed drawing conclusions, where disclosed that the company charged to revenue growth periods (2014-2015), compared to 5 the changes presented by the market, just as it was determined growth in operating expenses which affects the profit margin. As also increase liquidity will enable the company to have cash available to comply with its obligations. More than this the obligations the company has what has caused it is over indebted, will be diminished as recover debt on behalf of the company. Finally recommendations to company executives regarding better financial arrangements, obligations recover for the company, and reduce administrative costs proposed, this will have proper balance.